Morphology and vascularization of the corpus luteum of peccaries (Pecari tajacu, Linnaeus, 1758) throughout the estrous cycle - M.T.M. Miranda-Moura; G.B. Oliveira; G.C.X. Peixoto; J.M. Pessoa; P.C. Papa; M.S. Maia; C.E.B. Moura; M.F. Oliveira (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2016)
The current paper characterizes the changes in morphology and vascularization of the corpus luteum of collared peccaries during the estrous cycle and correlates progesterone synthesis (P4). Twenty females were subjected to a treatment for estrus synchronization; an ear implant containing 1.5 mg of norgestomet was implanted on D0, whereas on D9 the peccaries received an IM injection of eCG 200UI and 50g of PGF2a. The animals were divided into four groups (G1, G2, G3 and G4) and euthanized on post-ovulation days 3, 12, 18 and 22. The ovaries were collected and the corpora lutea were measured and processed for histological and vascular density (Dv). Blood was collected for dosage of P4 serum. The morphology of the ovaries, the corpora lutea and P4 varied significantly during the estrous cycle (P<0.001). There was a significant co-relationship between weight and length of the ovaries and CL (r = 0.66, r = 0.52, P<0.05, respectively) and between weight, length and width of the CL and P4 (r = 0.51, r = 0.54 and r = 0.68, P<0.05, respectively). The luteal Dv was highly influenced by the estrous cycle phase (P<0.0001). The P4 and luteal Dv concentrations were higher in G2 and evidenced maximum secretory activity, with a highly significant correlation (P<0.0001). Assessed lutein parameters may estimate the phase of the estrous cycle in peccaries and the functional activity of the corpus luteum.